Assessing the Stability of Psychological and Political Survey Measures. (January 2013) - Gerber, Alan S.; Huber, Gregory A.; Doherty, David; Dowling, Conor M.
Recent research demonstrates growing scholarly interest in the relationship between personality characteristics and political attitudes and behaviors. In this article we present analysis using data from a national panel survey conducted in two waves—the first prior to the 2010 U.S. midterm election, the second after it. We assess the stability of a variety of personality measures and find high correlations between the pre- and postelection measures. We also leverage the fact that Republicans made substantial gains in Congress in the 2010 election to determine whether various personality measures are affected by the intersection of partisan attachments and political events and find little evidence that they are. The findings provide encouraging evidence for those interested in examining the relationship between personality and political attitudes using survey data.